EFEKTIVITAS METODE BERCERITA DALAM MENGAJARKAN NILAI-NILAI ISLAM PADA ANAK SEKOLAH DASAR - Riski Ananda Nasution; Sery Bulan Harahap; Masrianti Ritonga (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to discuss the effectiveness of storytelling methods in teaching Islamic values to elementary school children. This research is qualitative and uses a literature study approach. The storytelling method is very interesting when applied as an education on the benefits provided by rice to provide moral, spiritual, and social messages so that it can be interesting and easy for children to understand. This study examines various literature and research that discusses the application of storytelling methods in the Islamic educational environment. The results of the study produced using the story method can help children understand Islamic values, such as honesty, compassion, and responsibility, more effectively because suffering can help children awaken their imagination and emotions toward the environment. In addition, if you tell a story that is in accordance with daily life, it will improve memory and it will be easy to understand the values that have been taught. Therefore, this method has the ability to be a tool in education that is fun and valuable for learning Islamic values in elementary school.